2008
DOI: 10.1016/j.jacc.2008.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Uptake of Minocycline and Mechanisms for In Vivo Cardioprotection

Abstract: Objectives The ability of minocycline to be transported into cardiac cells, concentrate in normal and ischemic myocardium and act as in vivo cardioprotector was examined. We also determined minocycline's capacity to act as a reducer of myocardial oxidative stress and matrix metalloproteinase (MMP) activity. Background The identification of compounds with the potential to reduce myocardial ischemic injury is of great interest. Tetracyclines (TTCs) are antibiotics with pleiotropic cytoprotective properties tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 32 publications
(54 reference statements)
4
43
0
2
Order By: Relevance
“…In our study, minocycline showed the highest potency in MMP-9 inhibition, which is in accordance with previous reports that introduced minocycline as an effective MMP inhibitor in pathological states, such as ischemic cardiac events, cerebral neurologic damage, and arthritis (28). As a result of accumulation and concentration in cardiac cells, minocycline provides cardio protection at lower doses (29). In addition, due to its lipophilicity, minocycline can pass through the bloodbrain barrier and provide neuroprotection at a high potency (low IC50) in comparison to other tetracyclines (18).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, minocycline showed the highest potency in MMP-9 inhibition, which is in accordance with previous reports that introduced minocycline as an effective MMP inhibitor in pathological states, such as ischemic cardiac events, cerebral neurologic damage, and arthritis (28). As a result of accumulation and concentration in cardiac cells, minocycline provides cardio protection at lower doses (29). In addition, due to its lipophilicity, minocycline can pass through the bloodbrain barrier and provide neuroprotection at a high potency (low IC50) in comparison to other tetracyclines (18).…”
Section: Discussionsupporting
confidence: 92%
“…The effective use of minocycline in brain diseases such as encephalomyelitis (16,31) and stroke (21) has been demonstrated, but this is the first report to demonstrate the effectiveness of minocycline in heart inflammation. In addition to down-regulation of MMPs, minocycline has several functions, including antiapoptotic and antioxidant actions (32,33). Therefore, it is possible that carioprotection may be also exerted by these mechanisms other than MMP suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding from neuroprotection to possible cardioprotection, several preclinical studies administered minocycline in cardioplegia and in ischemia/reperfusion injury models and found beneficial results. 17,18 Further studies investigated mechanisms and found that minocycline reduces/inhibits several important mediators of inflammation and apoptosis including high mobility group box 1 protein (HMGB1) an early mediator of inflammation and poly(ADP-ribose) polymerase-1 (PARP-1) extensively activated in ischemic tissue where it releases apoptotic-inducing factors. 19,20 In this current study, the investigators used micro-SPECT/CT imaging to demonstrate lower uptake of GSAO in risk regions of minocycline-treated rabbits compared to saline-treated control rabbits.…”
Section: See Related Article Pp 94-100mentioning
confidence: 99%